2019
DOI: 10.1186/s40663-019-0191-1
|View full text |Cite
|
Sign up to set email alerts
|

Understorey phylogenetic diversity in thermophilous deciduous forests: overstorey species identity can matter more than species richness

Abstract: Background: Understorey vegetation is a key biodiversity component of forest ecosystems. Previous studies examined its relations with the overstorey mainly in terms of taxonomic diversity, composition or productivity. So far, none focused on the phylogenetic aspect, which represents the deepest component of diversity in a community. Here, we explored the relations between overstorey species richness and identity and the phylogenetic structure of the understorey vegetation. As a model system we used a network o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Shifts occurred in the same direction in monospecific and mixed stands, though only in the latter these were significant due to cover variations and to, a lesser extent, species turnover. Changes were of different magnitude also depending on the focal tree species present in the overstorey, being smaller and not significant in the plots with the two more southern and drought-adapted species (either Q. ilex or Q. cerris) than in those with one of the three more mesophilous species (O. carpinifolia, C. sativa and Q. petraea; Coppi et al, 2019). While suggesting a possible tree species identity effect, this finding supports higher tolerance to water stress in understorey species of lowland mediterranean and sub-mediterranean woodlands, compared with those of more mesic forests at more northern latitudes or higher altitudes, as a result of the multiple drought adaptive traits of Mediterranean forest plants (Nardini et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Shifts occurred in the same direction in monospecific and mixed stands, though only in the latter these were significant due to cover variations and to, a lesser extent, species turnover. Changes were of different magnitude also depending on the focal tree species present in the overstorey, being smaller and not significant in the plots with the two more southern and drought-adapted species (either Q. ilex or Q. cerris) than in those with one of the three more mesophilous species (O. carpinifolia, C. sativa and Q. petraea; Coppi et al, 2019). While suggesting a possible tree species identity effect, this finding supports higher tolerance to water stress in understorey species of lowland mediterranean and sub-mediterranean woodlands, compared with those of more mesic forests at more northern latitudes or higher altitudes, as a result of the multiple drought adaptive traits of Mediterranean forest plants (Nardini et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…mixtures). For the purpose of this work, the only 5-species mixture plot was pooled together with the 4-species plots, as in Coppi et al (2019). Each species richness level was replicated with different species combinations of these trees, to separate species diversity from composition effects; the 27 species combinations represented in our design and the frequency of each species in the four richness levels are given in Supplementary Table 1.…”
Section: Study Site Sampling Design and Data Collectionmentioning
confidence: 99%
“…In addition, FDiv had a significant relationship with soil phosphorus content in middle‐aged LPs, which suggested that environmental factors have a certain degree of influence on functional diversity (Spasojevic & Suding, 2012), and the effects varied with the age of LPs. The possible reason is that the provenance of the regenerated woody plants was different, making the species of regenerated plants different with the age of LPs (Lu et al, 2014; Coppi et al, 2019; Sabatini et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the plant diversity of monoculture plantations is beneficial for promoting ecological functions and realizing the sustainable development of plantations (Zhang et al, 2021). In particular, understorey vegetation is an important component in the monoculture plantation ecosystem (Coppi et al, 2019). Studies have shown that understorey plants represent up to 80% of the plant species richness (Gilliam, 2007), and are critical for maintaining the functions of the plantation ecosystem (Chastain et al, 2006; Wayman & North, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Quercus petraea is a widely distributed species in central Europe, with several scattered populations in the Mediterranean region (Bruschi et al 2003), where it behaves as a mesophilous tree (Coppi et al 2019). The radial growth of this species proved to be affected by climate, with special reference to the spring air temperature and precipitation (Lebourgeois et al 2004).…”
Section: Discussionmentioning
confidence: 99%